Uveitis in patients with oligoarticular juvenile idiopathic arthritis and juvenile spondyloarthritis/enthesitis related arthritis: is there any difference? - A. Martins; S. Ganhão; F. Oliveira Pinheiro; C. Granjo Morais; M. Rodrigues; M. Leuzinger-Dias; L. Figueira; I. Brito (PAGEPress Publications, 2023)
Juvenile idiopathic arthritis (JIA) is the most common systemic disease causing uveitis in childhood and adolescence.